Pilot-scale evaluation of oxidant speciation, 1, 4-dioxane degradation and disinfection byproduct formation during UV/hydrogen peroxide, UV/free chlorine and UV/chloramines advanced oxidation process treatment for potable reuse. (1st November 2019) - Zhang, Zhong; Chuang, Yi-Hsueh; Szczuka, Aleksandra; Ishida, Kenneth P.; Roback, Shannon; Plumlee, Megan H.; Mitch, William A.
Abstract: Advanced oxidation using UV/free chlorine and UV/chloramines are being considered as alternatives to UV/H2 O2 for treatment of reverse osmosis (RO) permeate in treatment trains for the potable reuse of municipal wastewater. This pilot-scale comparison of the three advanced oxidation processes (AOPs) evaluated three factors important for selecting among these alternatives. First, the study characterized the speciation of oxidants serving as the source of radicals within the AOPs to facilitate process modeling. Kinetic modeling that included consideration of the chloramines occurring in RO permeate accurately predicted oxidant speciation. Modeling of the UV/free chlorine AOP indicated that free chlorine is scavenged by reactions with ammonia and monochloramine in RO permeate, such that oxidant speciation can shift in favor of dichloramine over the short (∼30 s) timescale of AOP treatment. Second, the order of efficacy for degrading the target contaminant, 1, 4-dioxane, in terms of minimizing UV fluence was UV/free chlorine > UV/H2 O2 ≫ UV/chloramines. However, estimates indicated that the UV/chloramines and UV/H2 O2 AOPs could be similar on a cost-effectiveness basis due to savings in reagent costs by the UV/chloramines AOP, provided the RO permeate featured >3 mg/L as Cl2 chloramines. Third, the study evaluated whether the use of chlorine-based oxidants within the UV/free chlorine and UV/chloramines AOPs enhanced disinfection byproduct (DBP) formation. Even after AOP treatment and chloramination, total halogenated DBP formation remained low at <15 μg/L for all three AOPs. DBP formation was similar between the AOPs, except that the UV/free chlorine AOP promoted haloacetaldehyde formation, while the UV/H2 O2 and UV/chloramines AOPs followed by chloramination increased chloropicrin formation. However, total DBP formation on a toxic potency-weighted basis was similar among the AOPs, since haloacetonitriles and haloacetamides were the dominant contributors and did not differ significantly among the AOPs. Graphical abstract: Image 1 Highlights: Mixtures of oxidants occur in AOPs at potable reuse facilities. A kinetic model could predict oxidant speciation in these AOPs. The order of efficacy for 1, 4-dioxane loss was UV/HOCl > UV/H2 O2 ≫ UV/chloramines. Halogenated DBP concentrations were similar for these AOPs.